Versatile bipolar temperature controller for custom in vitro applications. (October 2020) - Asteriti, Sabrina; Cangiano, Lorenzo
Graphical abstract: Highlights: Effective temperature control is crucial in many in vitro tissue studies. Electrophysiology or imaging often require specialized holding chambers. Our custom temperature controller offers versatility and highly optimized operation. Cooling and heating provide fast temperature changes over a wide physiological range. Step-by-step simple but theoretically rigorous instructions enable user optimization. Abstract: Effective temperature control is crucial in many studies of isolated biological tissues, with preparations often requiring specialized holding chambers. In these situations, the design flexibility and optimizations offered by a custom made temperature controller may be preferable over a commercial model. We present a versatile controller for heating and cooling applications, providing simple step-by-step instructions to mathematically model your specific system and optimize controller parameters. The apparatus uses analog components and linear stages to simplify circuit comprehension and customization, achieving fast transitions with small static errors and overshoots over a wide range of temperatures without readjustment. A fully featured rackable enclosure is complemented by two temperature probes based on the LMT70A linear microchip sensor (for the control loop and for bath monitoring). BNC outputs provide scaled probe signals for continuous temperature data acquisition. The maximum achievable power output of the controller is −23.5 W/+22.0 W (−4.7 V/+4.4 V, ±5.0 A), sufficient to bring a well designed holder for standard 35 mm chambers from 23 °C up to 37 °C in ~1 min and down to 3 °C in ~4 min. Any biologist with some technical prowess should be able to follow our instructions from modeling to assembly and calibration.